A influência do ambiente institucional e da imersão nas redes externas na transferência reversa de capacidades tecnológicas em multinacionais brasileiras - Bezerra, Maitê Alves (2014)
It is widely recognized that multinational enterprises' capabilities derive from its ability to acquire knowledge from different sources. However, with the recent emersion of emerging-market multinational enterprises (EMNE) scholars start asking how EMNEs capacities are built. As traditional MNEs, EMNEs seek knowledge in foreign markets. Although EMNEs tend to engage in technological asset-seeking, once they origin country lacks technological knowledge. Using the institutional and network approaches, I argue that the local institutional environment and the embeddedness in local networks jointly affect the reverse transfer of technological capabilities in EMNEs, specifically in Brazilian EMNEs. The sample is composed by a survey applied to 78 foreign Brazilian EMNEs subsidiaries and the data was analyzed through structural modeling equation, using the partial least square (PLS) approach. The results confirm that subsidiaries located in well-developed environments and highly embedded in local suppliers network are more likely to transfer technological product capabilities in to headquarter. Subsidiaries highly embedded in supplier and clients' local networks are more likely to transfer technological process capabilities to headquarter. However, the latter was only significant to subsidiaries established through acquisition. Another interesting finding is that Brazilian EMNEs subsidiaries seem to present low-performance in exploring local knowledge sources and that there is apparent evidence that Brazilian EMNEs engage more in market-seeking than knowledge-seeking FDI. Nevertheless, these evidences need to be better explored in future researches. With this research I hope to contribute to the extension of existing IB theory with a better understanding about reverse transfer of technological capabilities in EMNEs.